BIMBINGAN DAN KONSELING DI SEKOLAH KUNCI MENUJU SUKSES AKADEMIK DAN SOSIAL EMOSIONAL SISWA - Mira Fauziah; Muhammad Zaini; Mahdi NK (Program Studi Manajemen Pendidikan Islam, 2023)
Guidance and counseling are important pillars in basic education. This service not only focuses on students' academic problems, but also plays a crucial role in shaping their social and emotional character. This research aims to dig deeper into how guidance and counseling contribute to creating a conducive learning atmosphere and supporting overall student success. Through data analysis from various case studies and statistics, this research will examine the impact of guidance and counseling on improving students' academic achievement and emotional well-being. In other words, this research wants to show how guidance and counseling can help students not only achieve good grades, but also grow into individuals who are balanced and ready to face life's challenges